Employee Performance Optimization - Imam Perdana, Muhammad; Farida Ferine, Kiki (PT. Multidisciplinary Press Indonesia, 2024)
In this study, the researcher wants to see the direct and indirect influence between the motivation variable, work discipline as the independent variable and the organizational work environment as the moderating variable and employee performance as the dependent variable. This type of research uses quantitative, this research was conducted at BPJS Employment Branches throughout Medan Raya which consists of BPJS Employment Offices Medan City Branch, Medan Kisaran Branch, and Tanjung Morawa Branch. The population of this study was 82 employees and the sample used was the entire population using a saturated sampling technique. The data source used is a primary data source and data collection is carried out by distributing questionnaires. The research model used is phat analysis with smart PLS version 3.3.3. as a research measuring tool. The results of this research are as follows: Work discipline has a negative and insignificant effect on employee performance with an original sample value of -0.226 and a P value of 0.170. Work motivation has a positive and significant effect on employee performance with an original sample value of 0.474 and ap value of 0.003. Work discipline has a positive and significant effect on employee performance through the work environment indirectly with the original sample result being 0.542 and p value 0.000. Work Motivation has a negative and insignificant effect on employee performance through the work environment indirectly with an original sample value of -0.164 and ap value of 0.033.